Biff, Chip and Kipper stories. Stage 2, Stories, Group/guided reading notes - Tritton, Lucy (Oxford University Press Oxford, 2011)
Oxford Reading Tree market at Level 2 Key Stage 1/ Primary 1-3/ pupils Ages 4-7